The Influence of Financial Literacy, Financial Behavior, and Income on Investment Decisions (2018 Student Case Study for Management Study Program Universitas Muhammadiyah Sumatera Utara) - Sri Fitri Wahyuni; Radiman Radiman; Rita Nara (Journal of International Conference Proceedings (JICP), 2022)
An investment decision is to set aside some stages to try to obtain investment returns or profits in the future. One of the factors needed to make an investment is capital or funds. The author's goal is to see the effect of financial literacy, financial behavior, income from decisions on students of the faculty of economics, management study program class of 2018. The number of samples in this study were 84 and using the Slovin formula. The technical analysis in this study uses multiple linear regression analysis, multiple correlation, termination, t test and F test. The results of this study indicate that financial literacy (X1) has a positive and significant effect on entry decisions (Y). Financial behavior (X2) has no effect on successful decisions (Y). Income (X3) has no effect on successful decisions (Y). Financial literacy, financial behavior, income simultaneously have a significant effect on investing decisions (a case study of students of the 2018 class of management study program at the Muhammadiyah University of North Sumatra). Keywords: Financial Literacy, Behavior, Income, Investment Decisions.